PENGARUH HARGA KOMODITI PANGAN TERHADAP INFLASI DI KOTA MEDAN - Rahmanta Rahmanta; Yusak Maryunianta (JURNAL AGRICA, 2020)
Inflation greatly affects the regional economy. It can be enlarge positively and negatively. When considering a high area it has negative influence, which is considered to have an influence. If in a low area, it must be something positive that can be encourage improvement for the better. This study aims to analyze the majority of changes in food prices to conversion in Medan. The data used in this study are time series data from January 2014 to August 2019, the data used are secondary data consisting of the development of monthly food  prices and data analysis method used is VAR or VECM analysis. The result showed, in the short term inculding several variables that influence the price of rice one month earlier, the price of rice two months before, the price of red chili one month before, the price of red chili two months before, the price of cayenne pepper one month before, the price of cayenne pepper two month before, The price of onion two month before, the price of garlic two months before, one better variable length is a red chili.